APLIKASI MODUL SENSOR CAHAYA GY-302 BH1750 DAN SENSOR JARAK ULTRASONIK HC-SR04 PADA EKSPERIMEN FOTOMETER BERBASIS MIKROKONTROLER ARDUINO UNO - Muryani, Sri; Sumariyah, Sumariyah (BERKALA FISIKA, 2020)
This  study  aims  to  implement  the  GY-302  BH1750  light  sensor  module  and  the  HC-SR04 ultrasonic proximity sensor to determine the illumination of the test lamp and distance in an Arduino Uno-based photometer experiment.  There were aluminum rail with a total length of 100 cm and the sensor rail with length of 80 cm in the mechanical device of this photometer, while the sensor was made from acrylic. The working principle of this photometer experiment tool began with a DC motor that puts the sensor at the initial state near the limit switch 1. The sensor measured the illumination and distance to display on the LCD. The motor moved the sensor  away  from  the  lamp  and the  sensor  stopped  every  5  cm  change in  distance,  then  the sensor detected the distance and illuminates in which their values were displayed on the LCD. The motor returned to the limit switch 1 when it hits at the limit switch 2 of the limit finish. The average error value of the ultrasonic sensor calibration was 1.35% with the correlation value of 0.9997. Meanwhile the average error value of the light sensor calibration was 3.39% with the  correlation  value  of  0.9867.  The  results  of  this  photometer  experiment  showed  that  the intensity of the yellow, clear, red, and blue lights are 7.91, 6.42, 2.10, and 0.49 Cd with error values of 15.66, 11.61, 9.12, and 7.34% and the correlation values of 0.9954, 0.9983, 0.9987, 0.9981, respectively.Keywords: Photometer, light sensor, proximity sensor